Já podemos rir? Novas questões em cena por meio da trajetória do Asdrúbal trouxe o trombone (1970 – 1980) - Sena, Nathally Almeida (2018)
From the Cultural History perspective, this work aims to contribute to filling the existing gaps regarding the historical memory built between engagement and “desbunde” in the Brazilian theatrical scene. Taking as study experimental theater Asdrúbal Trouxe o Trombone: Trate-me Leão (1977); Aquela Coisa Toda (1980) and A Farra da Terra (1983) the discussions focused on experimental theater in the 1970s, as well as the institutionalized aesthetic standards, hierarchized and imposed by theatrical critics of the decade. The concept of Representation by Roger Chartier, showed itself before the survey of a problematic that helps us to think the work of art as object of analysis of historical research. The apprehension of the indications of reception and observation of theatrical critics was necessary for the understanding and exposition of the work of the group in the period, which foments and enables the debate between art and society. In this way it is a careful investigation, since the sources mentioned here have already been evaluated and hierarchized once.